Assessment and Validation of i-Skyradiometer Retrievals Using Broadband Flux and MODIS Data. (17th February 2014) - Dipu, S.; Pandithurai, G.; Panicker, A. S.; Takamura, T.; Lee, Dong-In; Kim, Dongchul
Abstract : Ground-based network of cloud measurements is presently limited and there exists uncertainty in the cloud microphysical parameters derived from ground-based measurements. Bias in the i-skyradiometer derived cloud optical depth (τ c ) and droplet effective radius (R eff ) and the importance of these parameters in the parameterization of clouds in climate models have made us intend to develop a possible method for improving these parameters. A new combination method, which uses zenith sky transmittance and surface radiation measurements, has been proposed in the present study to improve the retrievals. The i-skyradiometer derived parameters τ c and R eff have been provided as a first guess to a radiative transfer model (SBDART) and a new retrieval algorithm has been implemented to obtain the best combination of τ c and R eff having minimum bias (−0.09 and −2.5) between the simulated global and diffuse fluxes at the surface with the collocated surface radiation measurements. The new retrieval method has improved τ c and R eff values compared to those derived using the transmittance only method and are in good agreement with the MODIS satellite retrievals. The study therefore suggests a possible improvement of the i-skyradiometer derived cloud parameters using observed radiation fluxes and a radiative transfer model.